The consumption limit of oyster (Crassostrea cucullata born) is safe based on the heavy metal contents of Pb, Cu and Zn in the estuary of Los Kala River, Lhokseumawe City, Aceh Province - Emersida, Irfan (Universitas Malikussaleh, 2021)
Survey of heavy metal content in oysters (C. cucullata) in the waters of the Los Kala River estuary in June-July 2018. Heavy metal content analysis was carried out at the Riau KLHK Laboratory with Atomic Abortion Spectrophotometer Shimadzu AA-7000. The results showed that the heavy metal content in oysters (C. cucullata) was Pb (14,454 µg/g), Cu (103,778 µg/g), Cu (111,611 µg/g). The highest Pb content was found at Station II (16.0388 µg/g), the highest i Cu content was found at Station V (170.2445 µg/g), and the highest Zn content was found at Station II (128.7621 µg/g). In general calculations of Provisional Tolerable Weekly Intake(PTWI) set by FAO/WHO suggest that for health and to avoid the effects of heavy metals, consumption of oysters (C. cucullata) per person from the estuary of Los Kala River does not exceed 1.09 kg/week (based on Pb concentration), 21, 25 kg/week (based on Cu concentration) and 19.76 kg/week (based on Zn concentration).Keywords: C. cucullata, estuary of Los Kala River, Heavy metalcontent, PTWI